2011
DOI: 10.1002/cphc.201100492
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical Study on Cooperativity Effects between Anion–π and Halogen‐Bonding Interactions

Abstract: This article analyzes the interplay between lone pair-π (lp-π) or anion-π interactions and halogen-bonding interactions. Interesting cooperativity effects are observed when lp/anion-π and halogen-bonding interactions coexist in the same complex, and they are found even in systems in which the distance between the anion and halogen-bond donor molecule is longer than 9 Å. These effects are studied theoretically in terms of energetic and geometric features of the complexes, which are computed by ab initio methods… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
64
0
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 82 publications
(69 citation statements)
references
References 62 publications
4
64
0
1
Order By: Relevance
“…It is well established that the charge density q at the critical points (CPs) that emerge upon complexation give helpful information regarding the strength of the noncovalent interactions involved in the complexes [46,77]. Indeed they have been successfully used as a measure of the bond order in a variety of noncovalent interactions including anion-p and hydrogen-bonding and halogen-bonding interactions [48,78,79]. Therefore, the variation in the q value at CPs in multicomponent systems with respect to the isolated anion-p and rB complexes can be used to analyze the mutual influence of the two interactions.…”
Section: Aim Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…It is well established that the charge density q at the critical points (CPs) that emerge upon complexation give helpful information regarding the strength of the noncovalent interactions involved in the complexes [46,77]. Indeed they have been successfully used as a measure of the bond order in a variety of noncovalent interactions including anion-p and hydrogen-bonding and halogen-bonding interactions [48,78,79]. Therefore, the variation in the q value at CPs in multicomponent systems with respect to the isolated anion-p and rB complexes can be used to analyze the mutual influence of the two interactions.…”
Section: Aim Analysismentioning
confidence: 99%
“…A recent review has examined pairwise combinations of several weak interactions, including anion-p bonding, and described the synergy that operates between them [47]. In particular, the effect of the simultaneous interaction of the aromatic ring with hydrogen and halogen bond donor on the anion-p interaction has been recently studied [48]. In addition, the influence of metal coordination to heteroaromatic rings on the energetics of anion-p interactions has been analyzed in two papers [49,50].…”
Section: Introductionmentioning
confidence: 99%
“…Como esperado, a energia proveniente do potencial de troca de spins (E Ex (12) ) é sempre positiva, por se tratar de um termo repulsivo derivado do princípio da exclusão de Pauli. Embora o sistema (f) apresente uma contribuição ínfima de -1,71 kcal/mol para a energia eletrostática E (12) C,Resp , comparativamente os valores de -1,51 e -1,26 kcal/mol relacionados aos termos das energias de dispersão E D (20) 129 Canuto et al, 130 Frontera et al, 131 Parra et al 132 e em recente comunicação de Bauer e Spange.…”
Section: Métodos Teóricos De Decomposição De Energiaunclassified
“…In recent years, many studies on the properties and structures of anion-π bonds have been performed. In particular, Estarellas et al [40] revealed cooperativity effects when anion-π and halogen bond interactions coexist in the same complex.…”
Section: Introductionmentioning
confidence: 97%